Pengaruh Rasio Likuiditas, Rasio Profitabilitas Dan Ukuran Perusahaan Terhadap Financial distress Pada PT. Matahari Departement Store, Tbk - Asep Muhammad Lutfi; Aria Aji Priyanto; Ade Yusuf (CV. ULIL ALBAB CORP, 2024)
This study aims to analyze the influence of liquidity ratios, profitability ratios, and company size on Financial distress at PT Matahari Department Store Tbk during the period 2013-2022. The data used in this research is secondary data obtained from the company's annual financial reports. The research method used is a quantitative method with an associative approach. The results of the study show that liquidity has a significant effect on financial distress. High liquidity can reduce the risk of Financial distress by ensuring the company has enough cash to meet its short-term obligations. Profitability (ROA) does not show a significant effect on financial distress, indicating that slow-increasing profitability can disrupt cash flow and working capital. Company size also shows a significant effect on financial distress, where poorly managed growth can lead to increased costs and potential financial difficulties. This research provides important insights for the management of PT Matahari Department Store Tbk in managing financial risks and maintaining the operational stability of the company.